Influence of Bacterial Endotoxin on Mucosal Immune Response to Phosphorylcholine - Sapta Adisuka Mulyatno; Kosuke Kataoka; Makoto Fukui; Tselmeg Baatarjav Rita Cristina Orihuela Campos; Hiro-O Ito (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2012)
Bacterial lipopolysaccharide (LPS), a component of the outer membrane of gram-negative bacteriathat initiates inflammation by activation innate immune responses through Toll-like receptor 4(TLR4). However, the influence of LPS on the mucosal immune reactions remains to be addressed.This study was examined the effect of LPS in nasal vaccination model. BALB/c and C57BL/6 micewere nasally immunized with keyhole limpet hemocyanin (KLH) conjugated with hapten phosphorylcholine (PC) or trinitrophenol (TNP) with LPS as a mucosal adjuvant, in the presence orabsence of cholera toxin (CT). The antibody titers were measured in serum, saliva, and nasal washfluids by an enzyme-linked immunosorbent assay (ELISA) in IgM, IgG, and IgA isotype-specificmanner. The epitope-specific antibody production induced in blood and mucosal fluid was furtherenhanced by LPS for all isotypes examined. Besides, LPS, which has rarely been regarded as a mucosal adjuvant, was tested for its adjuvanticity by comparing the nasal immunization with PC-KLH plus LPS or with PC-KLH plus CT. LPS showed high adjuvanticity almost equal to CT. Possible differences of LPS from CT as a mucosal adjuvant remains to be elucidated.